Reforming Agricultural Trade for Developing Countries : Volume 2. Quantifyng the Impact of Multilateral Trade Reform - McCalla, Alex F. (Washington, DC: World Bank, 2013)
Reforming agricultural trade for developing countries is a two-volume set. The first volume is subtitled Key issues for a pro- development outcome of the Doha Round, and it is focused on specific concerns that are being encountered in the agricultural negotiations, and on strategies for dealing with them to arrive at a final agreement that will significantly spur growth and reduce poverty in developing countries. The companion volume is subtitled Quantifying the impact of multilateral trade reform. It comprises chapters that take different approaches to modeling trade reform and quantifying the resulting benefits and costs to various players in the negotiations. The study explains the differences in results that come out of these different approaches, and compares them to some other recent estimates of the gains from global trade reform.